Studies of an air cooler under frost condition - Cheng, Yeong Chang (2008)
Frost accumulation on an air cooler, a direct result of combined heat and mass transfer between the moist air flowing across a cold surface, causes heat transfer performance degradation due to the insulating effect of frost layer and the coil blockage as the frost grows. The complex geometry of finned tube air cooler leads to uneven wall and air temperature distribution inside the coil, and causes variations of frost growth rate and densification along the coil. In this study, a general distributed model with frost formation was developed to predict the dynamic behavior of an air cooler both under non-frost and frost condition. Results include frost accumulation and its effect on energy transfer, air off-coil temperature, refrigerant liquid dry-out position and propagation of frost formation along the coil.